Development of the Management of the Special Accounts As an Approach to Rationalization the General Budget in Algeria: Case of Revenue Regulation Fund - BOUFLIH, NABIL; TOURCHI, MOHAMED (The Arab Journal of Administration, 2018)
The study aims to emphasize the importance of developing and reforming the management of the special accounts of treasury as a most important instrument used in the management of the public finance in Algeria, by studying the largest Special Fund in Algeria Which is called Revenue Regulation Fund, the study found a many shortcomings in the management of the fund whether in the organizational side, or in the area working of the fund , or in levels of transparency and accountability, in the same context we have provided practical proposals to improving and developing the management of the fund and increasing its effectiveness In order to achieve the goal of rationalization of the general budget of the State , and maintain the stability of the financial policy of the state given the decline in public revenues due to lower oil prices in the international markets since 2014, in the same context The rejection of the development and adjustment of the Revenue Regulation Fund leads Algeria to bear the cost of losing the alternative opportunity of investing the Fund’s assets outside the country in order to generate additional returns and jeopardize the value of its assets as a result of high inflation. In conclusion, the main recommendations can be summarized as follows: The Fund should be provided with an organizational structure in line with its objectives and tasks and allow greater flexibility in its management. The need to train highly efficiency skills in the management of financial portfolios in global financial markets, and to benefit from the expertise and studies of researchers in the universities and in the specialized scientific institutes. The Fund’s investment strategy should focus on the need to achieve the primary objective of maximizing return with minimal risk. The proposed strategy should be flexible and adaptable to minimize the risks associated with the Fund’s investments. The need to strengthen cooperation relations with the leading countries in this field and to benefit from their experience in the management of the fund investments.